Stereotactic Radiosurgery for Intracranial Ependymomas: An International Multicenter Study. Issue 1 (28th March 2018) - Kano, Hideyuki; Su, Yan-Hua; Wu, Hsiu-Mei; Simonova, Gabriela; Liscak, Roman; Cohen-Inbar, Or; Sheehan, Jason P; Meola, Antonio; Sharma, Mayur; Barnett, Gene H; Mathieu, David; Vasas, Lucas T; et al.
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) is a potentially important option for intracranial ependymoma patients. OBJECTIVE: To analyze the outcomes of intracranial ependymoma patients who underwent SRS as a part of multimodality management. METHODS: Seven centers participating in the International Gamma Knife Research Foundation identified 89 intracranial ependymoma patients who underwent SRS (113 tumors). The median patient age was 16.3 yr (2.9-80). All patients underwent previous surgical resection and radiation therapy (RT) of their ependymomas and 40 underwent previous chemotherapy. Grade 2 ependymomas were present in 42 patients (52 tumors) and grade 3 ependymomas in 48 patients (61 tumors). The median tumor volume was 2.2 cc (0.03-36.8) and the median margin dose was 15 Gy (9-24). RESULTS: Forty-seven (53%) patients were alive and 42 (47%) patients died at the last follow-up. The overall survival after SRS was 86% at 1 yr, 50% at 3 yr, and 44% at 5 yr. Smaller total tumor volume was associated with longer overall survival ( P = .006). Twenty-two patients (grade 2: n = 9, grade 3: n = 13) developed additional recurrent ependymomas in the craniospinal axis. The progression-free survival after SRS was 71% at 1 yr, 56% at 3 yr, and 48% at 5 yr. Adult age, female sex, and smaller tumor volume indicated significantly better progression-free survival. Symptomatic adverse radiation effects were seen in 7 patients (8%). CONCLUSION: SRS provides another management option for residual or recurrent progressive intracranial ependymoma patients who have failed initial surgery and RT.